2020
DOI: 10.2478/ffp-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial wetwood of silver birch (Betula pendula roth): symptomology, etiology and pathogenesis

Abstract: The article is focused on microbiological and silvicultural properties of bacterial wetwood of silver birch (Betula pendula), also known as European white birch. During the active phase of the disease, bacterial wetwood (i.e. bacterial dropsy, vascular parenchymatous bacteriosis or flux slime) is characterised by crust and periderm bloating, necrotic wet stains and abundance of exudate. The disease is more likely to occur in older (r = 0.56, p < 0.01) and less-dense (r = −0.29, p < 0.01) stands.The stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Under natural conditions, the interaction in the systems "bacterium-bacterium", "bacterium-micromycete", "micromycete-bacterium" can and obviously should be different, because the micro-and microorganisms are influenced by various factors (woody plant at certain stages growth and development, its physiological state, the presence of a pathology, meteorological (synoptic) factors, including as catalysts of pathology, compliance of forest woody plant with forest conditions, etc.). However, experiments with coniferous forest woody plants have shown that phytopathogenic bacteria (so-called vital obligates) in natural conditions outside the pathological process do not affect the growth of micromycetes (Gvozdyak, 2005;Goychuk, 2020b). Studies of biological products ("Victant" and "P27ant") based on aerobic spore-forming bacteria Bacillus sp.…”
Section: біологія лісових та урбанізованих екосистемmentioning
confidence: 99%
“…Under natural conditions, the interaction in the systems "bacterium-bacterium", "bacterium-micromycete", "micromycete-bacterium" can and obviously should be different, because the micro-and microorganisms are influenced by various factors (woody plant at certain stages growth and development, its physiological state, the presence of a pathology, meteorological (synoptic) factors, including as catalysts of pathology, compliance of forest woody plant with forest conditions, etc.). However, experiments with coniferous forest woody plants have shown that phytopathogenic bacteria (so-called vital obligates) in natural conditions outside the pathological process do not affect the growth of micromycetes (Gvozdyak, 2005;Goychuk, 2020b). Studies of biological products ("Victant" and "P27ant") based on aerobic spore-forming bacteria Bacillus sp.…”
Section: біологія лісових та урбанізованих екосистемmentioning
confidence: 99%
“…In recent decades there has been epiphytotic dieback of the birch associated with vascular parenchymal bacteriosis, which has different names (bacterial dropsy, bacterial wet cancer, brown slime, watermark disease, "crying" of birch, "wetwood", "Slime flux", "alcoholic flux", etc., but a common etiology and pathogenesis. The causative agent of the bacterial dropsy of the birch in Ukraine is the polybiotroph Enterobacter nimipressuralis, the pathogenicity of which is proved in the experiment both during spring and autumn inoculation of experimental plants [2].…”
mentioning
confidence: 99%
“…Currently, bacteriosis and their pathogens are largely studied for plants of agrocenosis. As for the bacteriosis of forest trees, they have not been studied sufficiently, although in recent decades increased attention has been paid to this problem [1,2,3,4]. It is emphasized that on forest trees in the world several dozens of bacteriosis with different degrees of damage caused by bacteria of genera Pseudomonas, Xanthomonas, Enterobacter, Erwinia, Agrobacterium, Brenneria, Xylella, Rhizobium, Corynebacterium, Bacillus, Clostridium etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1952, he pointed out that the following bacterial species were isolated from various damage to oak in the forests of Ploiesti: Erwinia valachica Georg et Bod, Erwinia valachica f. onaca, Erwinia gueieicola Georg, et Bod. [26].…”
mentioning
confidence: 99%